Evaluasi Fitokimia dan Antioksidan dari Piper hispidum Sw. yang dikoleksi dari Desa Gunung Malang pada Vegetasi yang Berbeda - Vivi Anggia; Rindita Rindita; Fauziah Ulfa Ramadhany (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
Jamaican pepper (Piper hispidum Sw.) is a wild plant, member of Piperaceae family and invasive plant species reported used to heal wounds and treat symptoms of skin leishmaniasis. This study aims to explore phytochemicals of Piper hispidum, especially phenolic content and antioxidant capacity, in two diﬀerent abiotic condition of the forest, shaded and open area. Exploration of P. hispidum was conducted in Gunung Malang Village, Halimun Salak Mountain National Park (TNGHS). The sample was extracted with the ultrasonic method. The phenolic level and antioxidant activity were determined with Folin Ciocalteu and DPPH method where gallic acid was used as a standard. The total phenolic content assay showed 70% ethanol extract of P. hispidum Sw. leaves from the shaded and open forest were 17.4775 mg GAE/g and 12.6137 mg GAE/g of sample respectively. The antioxidant activity assay showed that IC50 of the sample from shaded and open forest were 94.8414 and 94.3412 ppm and gallic acid was 7.9817 ppm. This study showed that diﬀerences in vegetation and environmental abiotic factor may contributed in the amount of chemical compounds where open vegetation exposed to the sunlight had lower values than shaded but not signiﬁcantly aﬀected the antioxidant value.